Focused Review: Cytotoxic and Antioxidant Potentials of Mangrove-Derived Streptomyces - Ser, Hooi-Leng; Tan, Loh Teng-Hern; Law, Jodi Woan-Fei; Chan, Kok-Gan; Duangjai, Acharaporn; Saokaew, Surasak; Pusparajah, Priyia; Ab Mutalib, Nurul-Syakima; Khan, Tahir Mehmood; Goh, Bey-Hing; Lee, Learn-Han (Frontiers in Microbiology, 2017)
Human life expectancy is rapidly increasing with an associated increasing burden of chronic diseases such as neurodegenerative diseases and cancer; however there is limited progress in finding effective treatment for these conditions. For this reason, members of the genus Streptomyces have been explored extensively over the past decades as these filamentous bacteria are highly efficient in producing bioactive compounds with human health benefits. Being ubiquitous in nature, streptomycetes can be found in both terrestrial and marine environments. Previously, two Streptomyces strains (MUSC 137T and MUM 256) isolated from mangrove sediments in Peninsular Malaysia demonstrated potent antioxidant and cytotoxic activities against several human cancer cell lines on bioactivity screening. These results illustrate the importance of streptomycetes from underexplored regions aside from the terrestrial ecosystem. Here we provide the insights and significance of Streptomyces species in the search of anticancer and/or chemopreventive agents and highlight the impact of next generation sequencing on drug discovery from the Streptomyces arsenal.